Early outcomes of transforaminal percutaneous endoscopic lumbar discectomy for high school athletes with herniated nucleus pulposus of the lumbar spine. Issue 6 (November 2020) - Yamaya, Seiji; Okada, Yuki; Higashino, Kosaku; Sakai, Toshinori; Tezuka, Fumitake; Yamashita, Kazuta; Takata, Yoichiro; Nagamachi, Akihiro; Chikawa, Takashi; Sairyo, Koichi
Abstract : There are no reports in the literature on the clinical outcomes of percutaneous endoscopic lumbar discectomy (PELD) for high school athletes suffering from herniated nucleus pulposus (HNP) of the lumbar spine. PELD is a minimally invasive surgical procedure that can be performed under local anesthesia via an 8-mm skin incision. This study examined the outcomes of transforaminal PELD in high school athletes suffering from HNP. Subjects were 18 patients [14 males and four females; mean age 17 (15–18) years] who underwent PELD at our institutions. The events in which the patients competed were baseball (n = 6), softball (n = 2), rugby (n = 2), basketball (n = 2), table tennis (n = 2), American football (n = 1), wrestling (n = 1), track and field (n = 1), and dance (n = 1). All patients underwent PELD under local anesthesia. Back pain was assessed using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ) and a visual analog scale (VAS) before and after surgery. Time to return to competitive sport, complications, and rate of recurrence of herniation were examined. All factors assessed by the JOABPEQ were significantly improved after surgery. VAS score was also improved after surgery. Time to return to competitive sport was 7 weeks on average. The rate of return to play was 94.4%. There were no complications, such as dural tear, exiting nerve root injury, or hematoma. One patient had recurrence of HNP. PELD is a promising minimally invasive and effective procedure for high school athletes with HNP.